An efficient synthesis of the inimer gamma-(2-bromo-2-methylpropionate)-epsilon-caprolactone (BMPCL). Issue 3 (3rd July 2022) - Wright, Shannon E.; Clarkson, Aidan; Korns, Jenna M.; Haljun, Ellie; Lofving, Lila; Ourgessa, Meheret; Getzler, Yutan D. Y. L.
ABSTRACT: The original synthesis of gamma-(2-bromo-2-methylpropionate)-epsilon-caprolactone (BMPCL), in use since 1999, has an overall yield of 17% and uses a Cr (VI) reagent for a key oxidation. Despite these liabilities, this synthetic procedure has been reported in all subsequent uses of BMPCL. This is due to BMPCL's desirable capacity as an inimer – the tertiary alpha-bromo ester functionality allows initiation of controlled radical polymerization while the strained lactone moiety can act as a monomer in ring-opening polymerizations. These orthogonal capacities make BMPCL useful for the synthesis of complex polymer architectures such as combs. This paper reports a higher yielding, telescoped BMPCL synthesis that reduces the use of toxic reagents. Utilizing a mild and near-quantitative activated-DMSO mechanism, the Swern oxidation, in place of pyridinium chlorochromate increases the yield by approximately half to 25% (average of three trials) while eliminating heavy metal usage. In an additional effort for synthetic efficiency, the number of chromatographic purifications was reduced from three to one. GRAPHICAL ABSTRACT: UF0001